A synthesis of late Paleozoic and early Mesozoic sedimentary provenances and constraints on the tectonic evolution of the northern North China Craton. (November 2019) - Zhou, Rui; Liu, Dongna; Zhou, Anchao; Zou, Yu; Xie, Jinqiang
Graphical abstract: Highlights: The middle Permian sedimentary rocks were sourced from the Yinshan–Yanshan Orogen. The Yinshan–Yanshan Orogen was the main source for most areas of North China. The closure of the Paleo-Asian Ocean occurred between 267 and 261 Ma. The tectonic evolution of North China results from closure of the Paleo-Asian Ocean. Jurassic unconformity was recorded in response to the Late Triassic compression. Abstract: The North China Craton (NCC) and its adjacent areas experienced a series of complex tectonic events during the late Paleozoic–early Mesozoic, the closure of the Paleo-Asian Ocean (PAO), the collision between the Central Asian Orogenic Belt (CAOB) and the NCC, and the subduction of the Yangtze Plate. This paper provides an overview of the provenances and tectonic implications of late Paleozoic and early Mesozoic sediments in the northern NCC based on a comprehensive analysis of the available geological and geochronological data together with our new clast compositions, paleocurrents, detrital zircon ages and Hf isotope data. Detrital zircons from the middle Permian Shihezi Formation in the Yungang basin have age distributions of 442–264 Ma, 2179–1606 Ma and 2665–2249 Ma and are characterized by negative εHf (t) values that match the age population and Hf isotope peculiarities of the Yinshan–Yanshan Orogenic Belt (YYOB). These observations suggest that these zircons were derived from the YYOB, which is consistent with most regions of the NCC. The CAOB became a minor source of sediments in the northern NCC no earlier than the late Permian, and the ultimate closure time of the PAO can be constrained to 267–261 Ma by the youngest detrital zircon ages. The tectonic evolution of the northern NCC in the late Paleozoic was closely related to the southward subduction of the PAO and the amalgamation of the CAOB and the NCC. The angular unconformity underlying the Early Jurassic strata and the absence of Triassic strata in the Yungang basin might be ascribed to the continuous collision of the CAOB and the NCC during the Late Triassic.